How does green innovation enhance business sustainability? Systematic review and case study at PT PLN Indonesia Power UBP Suralaya - Reinardus Dwi Prio Christianto; Nur Wening; Rian Oktafiani; Ade Setiawan; Han Purnomo; Nuviah Herawati (Journal of Innovation in Business and Economics, 2025)
Green innovation (GI) plays a crucial role in business sustainability, particularly in the energy sector, as companies seek to balance environmental responsibility with economic viability. This study explores the impact of GI by integrating a systematic literature review with a case study of PT PLN Indonesia Power UBP Suralaya. Using a qualitative approach, the research combines Natural Language Processing (NLP) and Large Language Models (LLM) to analyze text data and identify key themes in green innovation. A meta-analysis of 26 Scopus-indexed documents was conducted to extract insights, which were then classified into clusters using LLM-based text analysis. The findings highlight that green innovation is shaped by three key factors: internal company dynamics (leadership, technology, and financial capital), external influences (government regulations and market demand), and academic research. To accelerate GI adoption, energy companies like PLN must take proactive measures, including: 1) strengthening strategic leadership with a well-defined Net Zero roadmap; 2) increasing investment in renewable technologies such as solar, wind, and smart grids; and 3) restructuring business models to incorporate Green Financing mechanisms. Without a fundamental transformation, GI efforts risk being confined to incremental improvements rather than leading to substantial progress in sustainability.